Selective Serotonin Reuptake Inhibitors Increase Urinary Free Cortisol in Patients with Carney Complex and Primary Pigmented Nodular Adrenocortical Disease - Chrysavgi Kamilaris, Crystal Dawn (J Endocr Soc, 2021)
Primary pigmented nodular adrenocortical disease (PPNAD) is a rare cause of ACTH-independent Cushing syndrome predominantly associated with Carney Complex (CNC), a multiple endocrine neoplasia syndrome primarily caused by inactivating defects in PRKAR1A. PPNAD, which has neuroendocrine features, demonstrates cortisol production in response to serotonin as well as increased expression of tryptophan hydroxylase type 2, a serotonin synthesizing enzyme, and the serotonin (5-HT) receptors types 4, 6, and 7. This creates an autocrine/paracrine serotonergic regulatory loop that activates cortisol production. PPNAD can be diagnosed through a 6-day Liddle test (LT) showing a paradoxical increase of >50% from baseline in 24-h urinary free cortisol (UFC) on the 2(nd) day of high-dose dexamethasone administration (Day 6). Selective serotonin reuptake inhibitors (SSRIs) inhibit the reuptake of serotonin and are widely used for the treatment of depression. We performed a retrospective cohort study of patients with CNC and PPNAD that underwent a LT to evaluate the effect of SSRIs on UFCs, with the hypothesis that SSRI use leads to an exaggerated increase in UFC through presumed activation of the described serotonergic regulatory loop. Of the 34 patients (4–65 y) with CNC and PPNAD that underwent a LT at our institution between 2004 and 2018, 4 took an SSRI during testing. No differences were observed between the SSRI (S) group and the non-SSRI (NS) group in baseline UFCs and the percent increase in UFC on D6. Specifically, the median (IQR) baseline UFC in the S group was 36 (13–252) mcg/24h (nl 4–56) vs 35 (13–98) mcg/24h in the NS group (P=0.95). The percent change in UFC was 208 (93–683)% in the S group and 185 (28–364)% in the NS group (P=0.89). However, there was a difference for overall UFC measurement (across days 1–6 of the LT) in the S group vs the NS group (P=0.03). Age <18 vs 18+ and sex did not have an effect on the outcomes (P=0.17 and P=0.74, respectively). Thus, we conclude that though the percent change in UFC during the LT was similar in both groups, there was a significant difference in overall UFC in the S group when compared to the NS group. These data support an effect of SSRIs and serotonin on UFC and consequently cortisol production in PPNAD. This interesting observation has to be confirmed in more patients with CNC and PPNAD to further elucidate the effects of SSRIs on cortisol production in patents with PPNAD-caused Cushing syndrome, as this may have significant diagnostic and therapeutic implications.